Distribution and Effect of Galanin on Gallbladder and Sphincter of Oddi Motility in the Pig. Issue 4 (1991) - Harling, Henrik; Messell, Tina; Jensen, Steen Lindkaer; Poulsen, Steen Seier
Abstract : This study was designed to determine the occurrence and topographical distribution of galanin-like immunoreactivity (GAL-LI) in the porcine gallbladder and sphincter of Oddi and to investigate the pharmacologic effect of GAL on gallbladder and sphincter of Oddi motility. By radioimmunoassay the concentration of GAL-LI in the gallbladder was 2.75 ± 0.23, 9.73 ± 1.33 in the common bile duct and 5.10 ± 0.37 in the sphincter of Oddi (pmol/g ± SE). By immunohistochemistry GAL-LI was found exclusively in ganglionic cells and in nerve fibers among the smooth muscle bundles. Gallbladder and sphincter of Oddi pressures were recorded before and during 5-minute local intraarterial infusion of 4, 8, 19, 39, 78 and 194 ng GAL-Kg -1 -min -1 in 12 anaesthetized pigs. GAL in doses ≥ 39 ng.kg -1 .min -1 significantly reduced sphincter of Oddi phasic wave frequency (4.8 ± 0.4 vs. 2.1 ± 0.5; p = 0.004) and sphincter of Oddi motility index (70.2 ± 6.02 vs. 27.7 ± 8.3; p = 0.002) but did not affect gallbladder pressure. We conclude that the distribution of GAL-LI in the sphincter of Oddi and the effect that a pharmacologic dose of GAL has on sphincter of Oddi motor activity, suggests that GAL may be involved in the physiologic control of bile flow in the pig.